Sunday
March 26, 2017

Post a New Question

Posted by on .

solve by completeing the square

m^2-9/2m=3/2

  • algebra - ,

    m^2 -9/2m = 3/2.
    m^2 -9/2m + (9/4)^2 = 3/2 + (9/4)^2
    m^2 - 9/2m +(9/4)^2 = 24/16 + 81/16
    m^2 -9/2m + (9/4)^2 = 105/16
    (m - 9/4)^2 = 105/16
    Take sqrt of both sides:
    m - 9/4 = (sqrt105)/4
    m = 9/4 + (sqrt105)/4 = (9 +- sqrt105)/4
    m = 4.8, and -0.31.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question